Polypropylene-based resin expanded beads, method for producing polypropylene-based resin expanded beads, and polypropylene-based resin expanded bead molded article
By using N-oxidized flame retardant amines in polypropylene resin foam particles and covering the polyethylene resin surface layer, the problem of poor fusion in the prior art is solved, and good flame retardant properties and fusion in thicker or developing molds are achieved.
Patent Information
- Application Number
- JP2021130797
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-10
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2041-08-10
AI Technical Summary
The prior art When using polypropylene resin foam particles containing flame retardant amines, the fusion property is poor, and it is difficult to obtain good flame retardant properties and fusion properties in thicker or developing foam molds.
Polypropylene resin foam particles containing N-oxidized flame retardant amines are used, and the surface is covered with a surface layer composed of a polyethylene resin. During the production process, the distribution ratio of N-oxidized flame retardant amine in the foam particles is controlled between 0.03% and 0.5%, and the distribution ratio of flame retardant amine on the surface is less than the proportion of the entire particle.
The polypropylene resin foam particles have good flame retardant properties and fusion properties in the mold, and are suitable for foam molds of general, thicker or developed shapes.
Smart Images

Figure 0007660460000010 
Figure 0007660460000011 
Figure 0007660460000012
Abstract
Description
[Technical field]
[0001] The present invention relates to an expanded polypropylene resin bead, a method for producing the expanded polypropylene resin bead, and a molded article made from the expanded polypropylene resin bead. [Background technology]
[0002] Polypropylene resin foamed bead moldings obtained by molding polypropylene resin foamed beads in a mold are used in various applications such as packaging materials, automobile parts, and building materials. In recent years, due to the diversification of applications of polypropylene resin foamed bead moldings, various foamed bead moldings such as thicker foamed bead moldings and lumpy foamed bead moldings are desired. The lumpy foamed bead molding refers to a molding in which the foamed beads constituting the foamed bead molding are fused to each other at a part of the surface of the foamed beads and have visible voids between the particles. The polypropylene resin foamed beads and polypropylene resin foamed bead moldings are produced, for example, as follows.
[0003] First, resin particles having a polypropylene resin as a base resin are dispersed in an aqueous medium containing an inorganic dispersant in a container. Next, the resin particles are impregnated with a foaming agent in the container, and the resin particles containing the foaming agent (expandable resin particles) are released from the container together with the aqueous medium to be expanded. In this way, expanded polypropylene resin particles are produced.
[0004] The polypropylene resin expanded bead molding is produced by filling the expanded beads produced as described above into a mold, supplying a heating medium such as steam, and forming the expanded beads into a desired shape. At this time, the expanded beads filled in the mold undergo secondary expansion and are fused to adjacent expanded beads by their surfaces melting.
[0005] The expanded polypropylene resin beads produced as described above may contain a hindered amine flame retardant in order to enhance the flame retardancy of an expanded bead molding produced using the expanded polypropylene resin beads (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2004-263033 A Summary of the Invention [Problem to be solved by the invention]
[0007] When the hindered amine flame retardant is added to the expanded polypropylene resin particles as described above in order to achieve the desired flame retardancy, there is room for improvement in the following respects. That is, when polypropylene resin foamed beads containing a hindered amine flame retardant are used for in-mold molding, the fusion property between the foamed beads tends to decrease. Therefore, depending on the expansion ratio of the foamed beads and the in-mold molding conditions, it may be difficult to obtain an expanded bead molding having the desired flame retardancy and excellent fusion property between the foamed beads. In particular, when an expanded bead molding having a thicker part or an expanded bead molding having a rice-rice-like shape is produced, there is room for improvement in the fusion property between the expanded beads.
[0008] The present invention has been made in consideration of the above background, and provides polypropylene-based resin expanded beads that can provide an expanded bead molding having excellent flame retardancy and excellent fusion properties between the expanded beads, a method for producing polypropylene-based resin expanded beads, and a polypropylene-based resin expanded bead molding. [Means for solving the problem]
[0009] The expanded polypropylene resin particles of the present invention are polypropylene resin particles containing a NOR type hindered amine, characterized in that the expanded polypropylene resin particles have a surface composed of a polyethylene resin composition containing a polyethylene resin, the blending ratio of the NOR type hindered amine in the expanded polypropylene resin particles is 0.03% by weight or more and 0.5% by weight or less, and the blending ratio of the NOR type hindered amine in the polyethylene resin composition is less than the blending ratio of the NOR type hindered amine in the expanded polypropylene resin particles (including 0).
[0010] The method for producing expanded polypropylene-based resin beads of the present invention includes a coating step of using a polypropylene-based resin as a base resin and coating a core layer containing a NOR-type hindered amine with a polyethylene-based resin composition, and an expansion step of expanding polypropylene-based resin particles having the core layer obtained by the coating step and a surface composed of the polyethylene-based resin composition to obtain expanded polypropylene-based resin beads, wherein the polypropylene-based resin particles have a blending ratio of the NOR-type hindered amine in the polypropylene-based resin particles of 0.03% by weight or more and 0.5% by weight or less, and the blending ratio of the NOR-type hindered amine in the polyethylene-based resin composition is less than the blending ratio of the NOR-type hindered amine in the polypropylene-based resin particles (including 0).
[0011] The expanded polypropylene resin beads of the present invention are characterized in that they are produced by molding the expanded polypropylene resin beads of the present invention in a mold. Effect of the Invention
[0012] The expanded polypropylene resin beads of the present invention contain a predetermined range of NOR type hindered amine, and the blending ratio of the NOR type hindered amine in the polyethylene resin composition constituting the surface of the expanded beads is lower than the blending ratio of the NOR type hindered amine in the entire expanded beads. The expanded polypropylene resin beads of the present invention can provide an expanded bead molding that maintains good flame retardancy and has excellent fusion properties between the expanded beads. Therefore, the expanded polypropylene resin beads of the present invention can be suitably used not only for general expanded bead moldings, but also for thicker expanded bead moldings and rice-shaped expanded bead moldings.
[0013] Furthermore, according to the method for producing expanded polypropylene resin beads of the present invention, expanded polypropylene resin beads that maintain good flame retardancy and also have excellent fusion properties between the expanded beads during molding in a mold can be produced satisfactorily.
[0014] The expanded polypropylene resin bead molding of the present invention is also excellent in flame retardancy and in fusion properties between the expanded beads. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1A is a cross-sectional view of a resin particle used in one embodiment of the manufacturing method of the present invention, and FIG. 1B is a cross-sectional view of a polypropylene-based resin expanded particle produced by expanding the resin particle shown in FIG. 1A. [Diagram 2] 2A and 2B are cross-sectional views for explaining the concept of the surface layer of a polypropylene resin expanded bead in one embodiment of the present invention, in which (2A) shows a surface layer consisting of a surface (coating layer), and (2B) shows a surface layer consisting of the surface (coating layer) and a portion of the expanded bead body. [Diagram 3] 1 is an example of a DSC curve obtained according to the method for measuring the heat of transition of plastics described in JIS K7122:1987 in order to obtain the total heat of fusion and the high-temperature peak heat of expanded beads. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The expanded polypropylene resin beads of the present invention, the method for producing the expanded polypropylene resin beads of the present invention, and the expanded bead molding of the present invention will be described below in order. Note that the method for producing the expanded polypropylene resin beads of the present invention may be simply referred to as the production method of the present invention below. In the description of the present invention, Figures 1 and 2 are used as appropriate. Fig. 1 is an explanatory diagram illustrating a part of an embodiment of the manufacturing method of the present invention. Fig. 1A shows a cross section of a polypropylene-based resin particle 10 used in an embodiment of the manufacturing method of the present invention, and Fig. 1B shows a cross section of an expanded polypropylene-based resin particle 20 manufactured by expanding the polypropylene-based resin particle 10 shown in Fig. 1A. Incidentally, the flame retardancy in the present invention refers to the performance evaluated based on the FMVSS302 combustion test.
[0017] [Polypropylene resin foam particles] As shown in FIG. (1B), the expanded polypropylene resin bead 20 of the present invention has a surface 22 composed of a polyethylene resin composition containing a polyethylene resin. In the following, the expanded polypropylene resin bead 20 may be simply referred to as the expanded bead 20. The polypropylene resin bead 10 may be simply referred to as the resin bead 10. The expanded beads 20 contain a NOR type hindered amine. The blending ratio of the NOR type hindered amine contained in the expanded beads 20 is 0.03% by weight or more and 0.5% by weight or less. By blending a sufficient amount of NOR type hindered amine in this manner, the expanded beads 20 and the expanded bead molding molded using the same can exhibit good flame retardancy. The expanded beads 20 are configured so that the blending ratio of the NOR hindered amine in the polyethylene resin composition described above is lower than the blending ratio of the NOR hindered amine in the expanded beads 20. Here, a low blending ratio of the NOR hindered amine in the polyethylene resin composition includes a case where the NOR hindered amine is 0% by weight in the polyethylene resin composition constituting the surface 22. By being configured as described above, the present invention can provide an expanded bead 20 that can be molded in a mold to produce an expanded bead molding having excellent fusibility while maintaining good flame retardancy.
[0018] As described above, flame-retardant polypropylene resin expanded beads (hereinafter, simply referred to as flame-retardant expanded beads) containing a NOR type hindered amine as a flame retardant have been known. Such flame-retardant expanded beads are generally produced by melt-kneading a base resin such as a polypropylene resin with a NOR type hindered amine to prepare a melt-kneaded mixture, granulating resin particles using the mixture, and expanding the resin particles. In the conventional flame-retardant expanded beads produced in this manner, the NOR type hindered amine is dispersed throughout the expanded beads. In other words, the NOR type hindered amine contained in the conventional flame-retardant expanded beads is blended to the same extent both on the surface of the expanded beads and on the center side of the expanded beads from the surface. Conventional flame-retardant expanded beads containing such NOR type hindered amines tended to have lower fusion properties between expanded beads than expanded beads not containing NOR type hindered amines. This tendency was found to be more pronounced when the bulk density of the expanded beads was low. The reason for this is unclear, but it was speculated that the relatively large amount of NOR type hindered amines present on the surface of the expanded beads inhibits fusion between the expanded beads during molding in a mold.
[0019] Even when a polyethylene resin having a low melting point is present on the surface of the expanded beads containing a NOR type hindered amine flame retardant, the expanded beads may not exhibit good fusion properties because the NOR type hindered amine is sufficiently blended on the surface. In particular, when a molded body having a thicker part or a moulded body having a lumpy shape is produced using the expanded beads containing a NOR type hindered amine flame retardant, there is room for improvement in the fusion properties between the expanded beads. The expanded bead molding having a thicker part refers to an expanded bead molding having a part with a thickness of 80 mm or more, for example. The expanded bead molding having a thicker part is prone to have poor internal fusion properties because steam does not easily reach the inside of the molding during molding in a mold. The thickness of the expanded bead molding means the thickness in the mold opening direction during molding of the expanded beads in a mold. In contrast, in the present invention, the surface of the expanded beads is formed using a polyethylene resin composition, and the blending ratio of the NOR type hindered amine in the polyethylene resin composition is adjusted to be lower than the blending ratio of the NOR type hindered amine in the polypropylene resin expanded beads, thereby exhibiting good flame retardancy and preventing a decrease in the fusion properties between the expanded beads.
[0020] The expanded beads 20 of the present invention will be described in more detail below. The expanded beads 20 have a surface 22 made of a polyethylene resin composition. The expanded beads 20 excluding the surface 22 may be referred to as an expanded bead body 21.
[0021] NOR type hindered amines: The expanded beads 20 contain the NOR hindered amine in a blending ratio ranging from 0.03% by weight to 0.5% by weight. If the blending ratio of the NOR hindered amine in the expanded beads 20 is too low, it becomes difficult to improve the flame retardancy of the expanded bead molding produced using the expanded beads 20. On the other hand, if the blending ratio of the NOR hindered amine in the expanded beads 20 is too high, the bubble diameter in the expanded beads 20 tends to become non-uniform, and there is a risk that the flame retardancy, surface properties, etc. of the resulting expanded bead molding will decrease.
[0022] In order to give a black appearance to the expanded bead molding produced using the expanded beads 20, carbon black may be added to the expanded beads 20. However, in general, expanded beads containing carbon black tend to be flammable. Therefore, from the viewpoint of making the resulting expanded bead molding less flammable even if the expanded beads 20 contain carbon black to an extent that they can be black, the blending ratio of the NOR type hindered amine in the expanded beads 20 is preferably 0.05% by weight or more, more preferably 0.06% by weight or more. On the other hand, from the viewpoint of improving the moldability of the expanded beads 20 in the mold, the blending ratio of the NOR type hindered amine in the expanded beads 20 is preferably 0.4% by weight or less, more preferably 0.35% by weight or less, and even more preferably 0.3% by weight or less.
[0023] The blending ratio of the NOR type hindered amine contained in the expanded beads 20 can be calculated from the blending ratio of the NOR type hindered amine in each material for producing the expanded beads 20, etc. For example, attention should be paid to the resin beads 10 prepared for producing the expanded beads 20. As shown in FIG. (1A), the resin beads 10 are materials for producing the expanded beads 20, and have a core layer 11 and a surface 12 composed of a polyethylene resin composition containing a polyethylene resin. The expanded beads 20 can be obtained by impregnating the resin beads 10 with a foaming agent and foaming them. The blending ratio of the NOR type hindered amine in the expanded beads 20 produced using this can be calculated from the relationship between the weight ratio of the core layer 11 and the surface 12, the blending ratio of the NOR type hindered amine in the core layer 11, and the blending ratio of the NOR type hindered amine in the surface 12.
[0024] Alternatively, the blending ratio of the NOR type hindered amine contained in the expanded beads 20 may be measured directly from the expanded beads 20. For example, the expanded beads 20 may be subjected to proton nuclear magnetic resonance ( 1 1H-NMR) or the like, the blending ratio of the NOR type hindered amine in the expanded beads 20 can be determined.
[0025] In the present invention, the NOR type hindered amine is a compound having an N-alkoxyl group (>N-OR) structure. Examples of the NOR type hindered amine include compounds having at least one skeleton of the following general formula (1). Any structure is bonded to R in general formula (1). For example, R in general formula (1) is exemplified by an alkyl group, a cycloalkyl group, an aralkyl group, an aryl group, etc. Also, examples of the alkoxyl group in general formula (1) are a cyclohexyloxy group, an octyloxy group, etc. [ka]
[0026] Preferred examples of the NOR type hindered amine used in the present invention include compounds represented by the following chemical formulas (2) to (4). Chemical formula (2) is the product name NOR116 (molecular weight 2261, manufactured by BASF), chemical formula (3) is the product name FP-T80 (molecular weight 681, manufactured by ADEKA Corporation), and chemical formula (4) is the product name Tinuvin 123 (molecular weight 737, manufactured by BASF). [ka] [ka] [ka]
[0027] The expanded beads 20 may contain one type of NOR hindered amine, or may contain two or more types of NOR hindered amine. The expanded beads of the present invention may contain, in addition to the NOR hindered amine, another flame retardant other than the NOR hindered amine. Examples of the other flame retardant include halogen-based flame retardants, phosphorus-based flame retardants, metal hydroxides, and hindered amines other than the NOR hindered amine represented by the above general formula (1). When the expanded beads 20 contain a flame retardant other than the NOR type hindered amine represented by general formula (1), the mixing ratio of the other flame retardant may be adjusted within a range that does not deviate from the spirit of the present invention.
[0028] When using expanded beads with low bulk density or expanded beads containing carbon black, it may be difficult to provide an expanded bead molding that stably exhibits good flame retardancy. From the viewpoint of stably exhibiting flame retardancy, the molecular weight of the NOR type hindered amine is preferably 400 to 2500, more preferably 500 to 1200. In addition, when using expanded beads containing a colorant such as carbon black, the color tone of the obtained expanded bead molding may become uneven. From the viewpoint of improving this problem, the molecular weight of the NOR type hindered amine is preferably 600 to 800. The reason why the above-mentioned problem is improved by setting the molecular weight in an appropriate range is not clear, but the following is considered. NOR type hindered amines with a molecular weight in the above range are easily mixed with the base resin constituting the expanded beads 20 and are difficult to aggregate in the base resin constituting the expanded beads 20. Therefore, aggregates of the NOR type hindered amine are unlikely to occur in the material, and the formation of bubble nuclei derived from the aggregates is suppressed. This is believed to reduce the variation in bubble diameter in the expanded beads and make the bubble thickness of the resulting molded article more uniform, which in turn leads to improved flame retardancy of the expanded bead molded article and less unevenness in color tone.
[0029] When one type of NOR type hindered amine is contained in the expanded beads 20, the molecular weight of the NOR type hindered amine is the sum of the atomic weights of the atoms constituting the NOR type hindered amine. On the other hand, when multiple types of NOR hindered amines are contained in the expanded beads 20, the molecular weight of the NOR hindered amine described above is the weighted average of the molecular weights of the NOR hindered amines contained in the expanded beads 20. When the molar ratio of each NOR hindered amine contained in the expanded beads 20 is unknown, the average molecular weight determined by GPC using polystyrene as the standard substance can be used as the molecular weight of the NOR hindered amine.
[0030] Carbon Black: From the viewpoint of providing an expanded bead molding having a black appearance, the expanded beads 20 preferably contain carbon black. From the viewpoint of easily obtaining an expanded bead molding having a good black appearance, the blending ratio of carbon black in the expanded beads 20 is preferably 0.5% by weight or more, more preferably 1.0% by weight or more, even more preferably 1.5% by weight or more, and particularly preferably 2.0% by weight or more. On the other hand, from the viewpoint of making the obtained expanded bead molding less flammable, the blending ratio of carbon black in the expanded beads 20 is preferably 5.0% by weight or less, more preferably 4.0% by weight or less, even more preferably 3.5% by weight or less, and particularly preferably 3.2% by weight or less. The blending ratio of carbon black in the expanded beads 20 or on the surface 22 of the expanded beads 20 described below can be calculated appropriately from the material used to produce the resin beads 10 . The blending ratio of carbon black in the expanded beads 20 or on the surface 22 of the expanded beads 20 described below may also be measured directly from the expanded beads 20 or a test piece cut out from the surface 22 of the expanded beads 20 described below. As a measurement method, a thermogravimetric differential thermal analyzer (i.e., TG-DTA) is used to perform measurements based on JIS K7120:1987 using the expanded beads 20 or the above test piece, and the blending ratio of carbon black contained can be determined based on the mass loss rate from 400°C to 1000°C in the obtained TG curve.
[0031] Examples of carbon black that can be used include channel black, roller black, furnace black, thermal black, acetylene black, ketjen black, etc. Among them, furnace black is preferable as the carbon black used in the present invention because it has an excellent balance between dispersibility in polypropylene-based resins and material costs.
[0032] The average cell diameter of the expanded beads 20 is preferably 50 μm or more, more preferably 80 μm or more, and even more preferably 100 μm or more from the viewpoint of improving moldability in a mold. Also, from the viewpoint of further suppressing unevenness in color tone of the expanded bead molding and improving surface smoothness, it is preferably 220 μm or less, more preferably 200 μm or less, and even more preferably 180 μm or less. Even when the average cell diameter of the expanded beads of the present invention is relatively small, such as in the above range, the expanded beads have good fusion properties with each other during molding in a mold. The average cell diameter of expanded beads is a value obtained as follows. First, a photograph is taken of a cross section of an expanded bead divided into two equal parts. A straight line is drawn on the photograph so as to roughly halve the area of the expanded bead cross section, and the length L of the line segment from one edge of an expanded bead to the opposite edge is divided by the number N of all the cells in contact with the line segment, giving the value (L / N) as the average cell diameter of one expanded bead. This operation is performed for 10 or more expanded beads, and the arithmetic average value is taken as the average cell diameter of the expanded beads.
[0033] Other Additives: The expanded beads 20 described above may contain any additives, such as a flame retardant, a flame retardant assistant, a cell regulator, a lubricant, a crystal nucleating agent, a colorant, a conductive material, and an antistatic agent.
[0034] Bulk density of foam particles: The bulk density of the expanded beads 20 is not particularly limited, but from the viewpoint of further increasing the rigidity of the expanded bead molding, it is preferably 10 kg / m 3 It is preferable that the saturation temperature is 15 kg / m or more. 3 More preferably, it is 18 kg / m or more. 3 More preferably, it is equal to or greater than this. Generally, when the bulk density of the expanded beads 20 is low, the amount of resin in the expanded beads 20 is small, and therefore the burning rate of the expanded beads 20 is likely to increase. However, in the present invention, a sufficient amount of NOR type hindered amine is blended in the expanded beads 20, so that good flame retardancy can be exhibited even when the bulk density is low. From the viewpoint of further improving the light weight of the expanded bead molding, the bulk density of the expanded bead 20 is 500 kg / m 3 It is preferable that the density is less than 100 kg / m 3 More preferably, it is 50 kg / m or less. 3 More preferably, it is 40 kg / m or less. 3 It is particularly preferred that: The method for adjusting the bulk density of the expanded beads 20 will be described later in the description of the manufacturing method of the present invention.
[0035] How to measure bulk density: The bulk density of the expanded particles 20 is measured by the following method. First, the expanded particles 20 to be measured are left to stand for 24 hours or more in an environment of 23°C temperature, 50% relative humidity, and 1 atm. The expanded particles having the weight W (g) thus obtained are filled into a measuring cylinder, and the filling height of the expanded particles in the measuring cylinder is stabilized by tapping the floor surface with the bottom of the measuring cylinder lightly several times. The bulk volume V (L) of the expanded particles indicated by the graduations on the measuring cylinder is read, and the weight W of the expanded particles is divided by the bulk volume V of the expanded particles (W / V). The value obtained in this way is expressed as kg / m 3 The bulk density of the expanded particles 20 (kg / m 3 ) can be obtained.
[0036] (Foam particle body) Base resin that constitutes the foamed bead body: The expanded bead body 21 is formed using a polypropylene resin as a base resin. Here, the base resin refers to a resin that accounts for 50% by weight or more of the 100% by weight of the resin that constitutes the expanded bead body 21. Examples of the polypropylene-based resin that is the base resin constituting the expanded bead body 21 include a propylene homopolymer or a polypropylene-based copolymer containing more than 50% by weight of structural units derived from propylene. The base resin may be one type of polypropylene-based resin or two or more types of polypropylene-based resins. Examples of the propylene homopolymer include polypropylene homopolymers such as isotactic polypropylene, syndiotactic polypropylene and atactic polypropylene. Examples of the polypropylene copolymer include copolymers of propylene and ethylene or α-olefins having 4 or more carbon atoms, such as propylene-ethylene copolymer, propylene-butene copolymer, and propylene-ethylene-butene copolymer, as well as propylene-acrylic acid copolymer, propylene-maleic anhydride copolymer, etc. These copolymers may be block copolymers, random copolymers, or graft copolymers. The above-mentioned polymer may be crosslinked, but is preferably non-crosslinked. From the viewpoint of moldability of the expanded beads in a mold, the polypropylene-based resin is preferably a polypropylene-based copolymer, more preferably one or more selected from a propylene-ethylene copolymer, a propylene-butene copolymer, and a propylene-ethylene-butene copolymer, and further preferably a propylene-ethylene copolymer. In addition, in the present invention, a material that contains a polypropylene-based resin as a base resin and a NOR-type hindered amine and that constitutes the expanded bead body 21 may be referred to as a polypropylene-based resin composition. In addition to the above, the polypropylene-based resin composition may contain other polymers other than the polypropylene-based resin as a base resin and any additives within the scope of the present invention.
[0037] Other polymers: Examples of other polymers include thermoplastic resins other than polypropylene resins, such as polyethylene resins, polystyrene resins, polyamide resins, and polyester resins, and elastomers, such as olefin thermoplastic elastomers and styrene thermoplastic elastomers. Two or more of these other polymers may be included. The blending ratio of other polymers in the resin constituting the expanded bead body 21 is preferably 30% by weight or less, more preferably 20% by weight or less, even more preferably 10% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 0% by weight, i.e., it is most preferable that the expanded bead body 21 contains only polypropylene-based resin as a polymer.
[0038] Melting point of the resin that composes the foamed bead body: From the viewpoint of obtaining an expanded bead molded body having excellent mechanical properties such as rigidity while maintaining the moldability of the expanded beads 20, the melting point of the resin constituting the expanded bead body 21 is preferably 130° C. or more and 150° C. or less, more preferably 132° C. or more and 145° C. or less, and even more preferably 135° C. or more and 140° C. or less. The melting point of the resin here refers to the melting point of the polypropylene resin when the resin constituting the expanded bead body 21 is substantially one type of polypropylene resin. Also, when the resin constituting the expanded bead body 21 is a mixture of two or more types of polypropylene resins or a mixture containing one or more types of polypropylene resins and other resins, it refers to the melting point of a kneaded product obtained by kneading the mixture in advance with an extruder or the like.
[0039] The melting point of the resin constituting the expanded bead body 21 can be determined based on JIS K7121:1987. In this case, the condition adjustment of the test piece is performed as described in "(2) Measuring the melting temperature after performing a certain heat treatment". More specifically, based on the heat flux differential scanning calorimetry described in JIS K7121:1987, a test piece of 2 mg of pellet-shaped base resin is heated from 23°C to 200°C at a heating rate of 10°C / min, cooled to 23°C at a cooling rate of 10°C / min, and then heated again from 23°C to 200°C at a heating rate of 10°C / min. The melting point of the resin is determined by the apex temperature of the melting peak determined by the DSC curve obtained when the test piece is heated from 23°C to 200°C at a heating rate of 10°C / min. When two or more melting peaks appear in the DSC curve, the apex temperature of the melting peak with the largest area is determined as the melting point. Moreover, examples of the measuring device include a heat flux differential scanning calorimeter (manufactured by SII NanoTechnology, Inc., model number: DSC7020).
[0040] (Surface of foam particles) Next, the surface 22 of the expanded bead 20 will be described. The expanded beads 20 have a surface 22 composed of a polyethylene resin composition containing a polyethylene resin. FIG. (1A) shows a resin particle 10 having a resin particle body 11 and a surface 12. FIG. (1B) shows an expanded particle 20 produced using the resin particle 10. The surface 22 is a surface resulting from the surface 12. When the resin particle 10 is obtained by a co-extrusion method described later, the resin particle 10 has a resin particle body 11 and a coating layer 12S that covers the resin particle body. The coating layer 22S of the expanded particle 20 is a coating layer resulting from the coating layer 12S. The coating layer 22S may be a foamed layer or a non-foamed layer. The non-foamed layer means a layer that does not substantially have a bubble structure. The coating layer 22S may be partially foamed.
[0041] The surface 22 (coating layer 22S) is composed of a polyethylene resin composition that does not contain a NOR type hindered amine, or a polyethylene resin composition that contains a NOR type hindered amine in a proportion that is less than the proportion of NOR type hindered amine contained in the entire expanded beads 20. This allows the proportion of NOR type hindered amine in the surface 22 of the expanded beads 20 to be adjusted to be low, making it possible to improve the fusion property between the expanded beads 20 during molding in a mold while maintaining the flame retardancy of the expanded beads 20.
[0042] Polyethylene resin composition constituting the surface: The polyethylene resin composition constituting the surface 22 is a composition containing a polyethylene resin as a base resin. From the viewpoint of the fusibility of the expanded beads, it is preferable that the polyethylene resin, which is the base resin of the polyethylene resin composition, has a melting point or softening point lower than the melting point of the polypropylene resin constituting the expanded bead body 21. The polyethylene resin composition may contain other polymers than the polyethylene resin and any additives within the scope of the present invention.
[0043] Base resin contained in polyethylene resin composition: The base resin contained in the polyethylene resin composition is a polyethylene resin. The polyethylene resin accounts for 50% by weight or more of the resin contained in the polyethylene resin composition (100% by weight). The base resin may be one type of polyethylene resin or two or more types of polyethylene resins. The polyethylene resin is exemplified by an ethylene homopolymer or a polyethylene copolymer containing more than 50% by weight of structural units derived from ethylene.
[0044] Examples of polyethylene resins include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), high-density polyethylene (HDPE), ethylene-vinyl acetate copolymer, ethylene-acrylic acid copolymer, ethylene-methacrylic acid copolymer, ethylene-alkyl methacrylic acid ester copolymer, etc. These copolymers may be any of block copolymers, random copolymers, and graft copolymers. Among them, from the viewpoint of suppressing peeling between the expanded bead body 21 and the surface 22 (coating layer 22S), the polyethylene resin is preferably one or more selected from low-density polyethylene, linear low-density polyethylene, and high-density polyethylene, and more preferably linear low-density polyethylene. Low-density polyethylene has a long-chain branched structure and a density of 910 kg / m 3 More than 930kg / m 3 Linear low-density polyethylene refers to a polyethylene resin having a molecular weight of less than 910 kg / m. Linear low-density polyethylene is a copolymer of ethylene and an α-olefin having 4 to 8 carbon atoms, and has a substantially linear molecular chain and a density of 910 kg / m. 3 More than 930kg / m 3 High density polyethylene refers to a polyethylene resin having a density of less than 930 kg / m. High density polyethylene is an ethylene homopolymer or a copolymer of ethylene and an α-olefin having 4 to 8 carbon atoms, and has a density of 930 kg / m 3 This refers to the above polyethylene resins.
[0045] In one preferred embodiment of the present invention, the polyethylene resin composition contains, as a base resin, a linear low-density polyethylene polymerized using a metallocene polymerization catalyst. It is more preferred that the polyethylene resin contained in the polyethylene resin composition constituting the surface 22 is substantially only linear low-density polyethylene polymerized using a metallocene polymerization catalyst. The surface 22 (coating layer 22S) made of a polyethylene resin composition containing linear low-density polyethylene polymerized using a metallocene polymerization catalyst is particularly likely to be inhibited from peeling off from the expanded bead body 21. Therefore, the expanded beads 20 having the surface 22 containing the linear low-density polyethylene exhibit good fusibility, while the surface 22 is unlikely to adhere to a molding die during molding in the mold.
[0046] Other polymers contained in the polyethylene resin composition: Examples of other polymers include thermoplastic resins other than polyethylene resins, such as polypropylene resins, polystyrene resins, polyamide resins, and polyester resins, and elastomers, such as olefin thermoplastic elastomers and styrene thermoplastic elastomers. Two or more of these other polymers may be included. The blending ratio of other polymers in the polyethylene-based resin composition is preferably 30% by weight or less, more preferably 20% by weight or less, even more preferably 10% by weight or less, even more preferably 5% by weight or less, particularly preferably 3% by weight or less, and most preferably 0% by weight, i.e., the polyethylene-based resin composition contains only polyethylene resin as the polymer.
[0047] Melting point of resin contained in polyethylene resin composition: The melting point of the polyethylene resin contained in the polyethylene resin composition is preferably 100° C. or more and 125° C. or less, more preferably 105° C. or more and 120° C. or less. The melting point difference [Tmc-Tms] between the melting point Tms of the polyethylene resin contained in the polyethylene resin composition and the melting point Tmc of the polypropylene resin constituting the expanded bead body 21 is preferably more than 0 and 35° C. or less, more preferably 5° C. or more and 32° C. or less, and even more preferably 10° C. or more and 30° C. or less. This allows the surface 22 to function as a fusion layer that enhances the fusion property between the expanded beads 20 during in-mold molding, and the fusion property between the expanded beads 20 during in-mold molding can be further enhanced.
[0048] The softening point (Vicat softening temperature) of the polyethylene resin is measured based on the A50 method of JIS K7206:2016. The melting point of the polyethylene resin is measured based on JIS K7121:1987, similar to the melting point of the polypropylene resin constituting the foamed bead body 21. However, when two or more melting peaks appear in the DSC curve, the temperature at the apex of the melting peak on the lowest temperature side is regarded as the melting point. The melting point of the polyethylene resin constituting the surface 22 is equal to the melting point or softening point of the polyethylene resin constituting the surface 12 of the resin particle 10 used to produce the expanded beads 20. Therefore, by measuring in advance the melting point or softening point of the polyethylene resin constituting the surface 12 of the resin particle 10 according to the above-mentioned measurement method, the melting point of the polyethylene resin constituting the surface 22 of the expanded beads 20 can be grasped.
[0049] Surface (coating layer) ratio in foam beads: The weight ratio of the surface 22 (coating layer 22S) in the expanded beads 20 is preferably 0.5% by weight or more and 20% by weight or less. This provides a good balance between the surface 22 (coating layer 22S) and the expanded bead body 21, and the expanded bead molding produced using such expanded beads 20 has excellent fusion properties and excellent mechanical properties. From the viewpoint of more stably improving the fusion properties between the expanded beads 20, the weight ratio of the surface 22 (coating layer 22S) in the expanded beads 20 is more preferably 1% by weight or more, even more preferably 3% by weight or more, and particularly preferably 5% by weight or more. On the other hand, from the viewpoint of further improving the mechanical properties of the expanded bead molding, the weight ratio of the surface 22 (coating layer 22S) in the expanded beads 20 is preferably 15% by weight or less, more preferably 12% by weight or less, and even more preferably 10% by weight or less. As long as the intended object of the present invention is achieved, the surface 22 made of a polyethylene resin composition may be provided on the entire surface of the expanded beads 20, or may be provided on only a portion of the surface.
[0050] Carbon Black: In order to impart a good black appearance to an expanded bead molding produced using the expanded beads 20, it is preferable that carbon black is also blended into the polyethylene resin composition constituting the surface 22. By blending carbon black not only into the expanded bead body 21 but also into the polyethylene resin composition constituting the surface 22, it is possible to provide a black expanded bead molding with reduced unevenness in color tone. From the viewpoint of easily obtaining an expanded bead molding with a good appearance in which unevenness in color tone is sufficiently suppressed, the blending ratio of carbon black in the polyethylene resin composition constituting the surface 22 is preferably 0.5% by weight or more, more preferably 1.0% by weight or more, even more preferably 1.5% by weight or more, and particularly preferably 2.0% by weight or more. On the other hand, from the viewpoint of improving the moldability of the expanded beads 20 in the mold and making the resulting expanded bead molding less flammable, the blending ratio of carbon black in the polyethylene resin composition constituting the surface 22 is preferably 5.0% by weight or less, more preferably 4.0% by weight or less, even more preferably 3.5% by weight or less, and particularly preferably 3.2% by weight or less. For the carbon black optionally added to the polyethylene resin composition, the above description regarding the carbon black added to the expanded bead body 21 may be referred to as appropriate.
[0051] Other Additives: Within the scope of the present invention, the polyethylene resin composition constituting the surface 22 may further contain one or more other additives. Examples of the other additives include flame retardants other than NOR-type hindered amines, flame retardant assistants, lubricants, crystal nucleating agents, colorants, conductive materials, antistatic agents, and the like. However, the polyethylene resin composition constituting surface 22 preferably contains, in addition to a polymer (including a base resin), substantially only carbon black and / or a NOR type hindered amine as an additive, more preferably substantially only carbon black, and may be composed substantially only of a polymer (including a base resin).
[0052] NOR type hindered amines: The polyethylene resin composition constituting the surface 22 may contain a NOR type hindered amine in an amount less than the blending ratio of the NOR type hindered amine in the expanded polypropylene resin particles. More specifically, the blending ratio of the NOR type hindered amine in the polyethylene resin composition is preferably 0.2% by weight or less, more preferably 0.15% by weight or less, and even more preferably 0.1% by weight or less. From the viewpoint that the fusion property between the expanded beads 20 can be stably increased even though the base resin constituting the expanded beads 20 is a polypropylene resin having a high melting point, the blending ratio of the NOR type hindered amine in the polyethylene resin composition is preferably substantially 0. On the other hand, from the viewpoint of maintaining good fusion property between the expanded beads 20 and exhibiting higher flame retardancy, the blending ratio of the NOR type hindered amine in the polyethylene resin composition is preferably 0.01% by weight or more, more preferably 0.02% by weight or more, and even more preferably 0.05% by weight or more. For the NOR type hindered amine optionally added to the polyethylene resin composition, the above description regarding the NOR type hindered amine added to the expanded bead body 21 may be referred to as appropriate.
[0053] Ratio of the blending ratio of the NOR type hindered amine in the polyethylene resin composition constituting the surface 22 to the blending ratio of the NOR type hindered amine in the expanded beads 20: The expanded beads 20 have a surface 22 composed of a polyethylene resin composition, and the blending ratio of the NOR type hindered amine in the polyethylene resin composition is smaller (including 0) than the blending ratio of the NOR type hindered amine in the expanded beads 20. In other words, the ratio of the blending ratio of the NOR type hindered amine in the polyethylene resin composition constituting the surface 22 to the blending ratio of the NOR type hindered amine in the expanded beads 20 is less than 1. The ratio of the NOR type hindered amine content in the polyethylene resin composition constituting the surface 22 to the NOR type hindered amine content in the expanded beads 20 is preferably 0.5 or less, more preferably 0.3 or less, even more preferably 0.1 or less, and most preferably 0, from the viewpoint of further enhancing the fusion properties between the expanded beads 20.
[0054] Whether or not the blending ratio of the NOR type hindered amine in the polyethylene resin composition is lower than the blending ratio of the NOR type hindered amine in the expanded beads 20 can be confirmed as follows. The blending ratio of the NOR hindered amine in the expanded beads 20 means the blending ratio of the NOR hindered amine in the entire resin beads 10 used to produce the expanded beads 20. Moreover, the blending ratio of the NOR hindered amine in the polyethylene resin composition means the blending ratio of the NOR hindered amine in the polyethylene resin composition constituting the surface 12 (coating layer 12S) of the resin beads 10 used to produce the expanded beads 20. Therefore, the blending ratio of the NOR hindered amine in the entire expanded beads 20 and in the polyethylene resin composition can be known from the blending ratio of each material in the production process of the resin beads 10.
[0055] In addition, when the mixing ratio of each material in the manufacturing process of the resin beads 10 is unknown, the mixing ratio of the NOR type hindered amine in the entire expanded beads 20 and in the polyethylene resin composition roughly corresponds to the content ratio of the NOR type hindered amine in the entire expanded beads 20 and in the polyethylene resin composition, respectively. Therefore, by measuring the content ratio of the NOR type hindered amine using the expanded beads 20, it is also possible to confirm whether the mixing ratio of the NOR type hindered amine in the polyethylene resin composition is less than the mixing ratio of the NOR type hindered amine in the expanded beads 20. For example, the content ratio of the NOR type hindered amine in the expanded beads 20 may be directly measured by using the entire expanded beads 20 as a measurement sample. Also, the content ratio of the NOR type hindered amine in the polyethylene resin composition may be directly measured by taking a part of the polyethylene resin composition located on the surface of the expanded beads 20 as a measurement sample. Specifically, the measurement sample is subjected to proton nuclear magnetic resonance ( 1 The content of NOR-type hindered amine in the measurement sample can be determined by subjecting the sample to NMR (H-NMR) or the like.
[0056] When it is difficult to cut out only a part of the polyethylene resin composition from the expanded beads 20, or when it is unclear whether only a part of the polyethylene resin composition has been cut out, it is advisable to use the concept of the surface layer (surface layer 30) of the expanded beads 20. The surface layer (surface layer 30) of the expanded beads 20 will be described with reference to Fig. 2. Fig. 2 is a cross-sectional view of the expanded beads 20. In the expanded beads 20, the surface layer 30 refers to a region having a certain thickness from the outermost surface of the portion of the expanded beads 20 made of the polyethylene resin composition toward the center of the expanded beads 20. For example, when the surface 22 made of the polyethylene resin composition is configured as a layer having a sufficient thickness to enable cutting out only that portion, the surface layer 30 refers to that layer. In this case, the surface layer 30A of the expanded beads 20 shown in FIG. (2A) corresponds to this. On the other hand, when the surface 22 is made of the polyethylene resin composition but does not have a thickness to enable cutting out only that portion, the surface layer 30 refers to a region (surface layer 30B in FIG. (2B)) that includes the surface 22 made of the polyethylene resin composition and includes a part of the expanded bead body 21. Regardless of whether the surface layer 30 is the surface layer 30A or the surface layer 30B, the surface layer 30 is cut out from the expanded beads 20 to prepare a measurement sample, and the measurement sample is subjected to proton nuclear magnetic resonance ( 1 The content of the NOR type hindered amine in the surface layer 30 can be determined by subjecting the surface layer 30 to measurement using 1 H-NMR or the like. In addition, the entire expanded beads 20 were used as a sample, and the sample was subjected to proton nuclear magnetic resonance ( 1The content of the NOR type hindered amine in the expanded beads 20 can be determined by subjecting the expanded beads 20 to measurement using 1 H-NMR or the like. The NOR type hindered amine contents obtained by these measurements are then compared, and if the NOR type hindered amine content in the surface layer 30 is lower than the NOR type hindered amine content in the entire expanded beads 20, it can be determined that the NOR type hindered amine content in the polyethylene resin composition is lower than the NOR type hindered amine content in the expanded beads 20.
[0057] The pretreatment method of the measurement sample and the proton nuclear magnetic resonance ( 1 The following method can be used to quantify the content of NOR-type hindered amine in a measurement sample by H-NMR, for example. The measurement sample is first pretreated by freeze-pulverizing the measurement sample and weighing out about 2 mg. Then, Soxhlet extraction is performed using chloroform as a solvent to remove the insoluble polymer components. The soluble portion from the Soxhlet extraction is added to acetone to remove the acetone-insoluble oligomer components. The acetone-soluble portion is concentrated, dried, and solidified, and used as the measurement sample for proton nuclear magnetic resonance ( 1 The mixture is subjected to measurement by H-NMR. Proton nuclear magnetic resonance ( 1 For example, an AL-400 model manufactured by JEOL Ltd. can be used as the 1H-NMR spectrometer. Solvent: CDCl 3 , measuring nuclei: 1 H, internal standard sample: tetrachloroethane (TCE) is used.
[0058] How to check the resin that makes up the foam particles: Next, a method for confirming the resin constituting the expanded beads 20 will be described. The expanded beads 20 have an expanded bead body 21 made of a polypropylene-based resin composition containing a polypropylene-based resin as a base resin, and a surface 22 made of a polyethylene-based resin composition containing a polyethylene-based resin as a base resin on the outer peripheral surface of the expanded bead body 21. The fact that the expanded beads 20 have such a structure can be determined by an attenuated total reflection (ATR) method using infrared rays. Specifically, it can be determined by checking the infrared absorption spectrum of the surface and cross section of the expanded beads 20 measured by the ATR method.
[0059] The ATR method is a technique in which infrared light is incident on a sample surface with a prism in close contact with it, and the infrared light penetrates slightly into the sample when it is totally reflected by the sample surface, to measure the infrared spectrum from the sample surface to a depth of several micrometers. The ATR method is widely used for surface analysis of various materials because it is easy to measure the spectrum by simply contacting the sample with a prism. However, in the ATR method, the penetration depth into the sample varies depending on the refractive index of the prism material and the angle of incidence of the infrared light, as shown in the following formula (Equation 1). Therefore, when measuring non-uniform materials, it is desirable to keep the measurement conditions constant. For example, it can be seen from the following formula (1) that when the angle of incidence is increased or when a prism with a large refractive index is used, the penetration depth becomes shallower.
number
[0060] A specific method for measuring the infrared absorption spectrum of the surface of the expanded beads 20 by the ATR method will be described below. First, prepare the measurement device used for the ATR method and measure the following conditions at 340 kg / cm 2The surface of the expanded beads is brought into close contact with the prism at a pressing pressure of 1000 MPa, infrared light is incident, and the totally reflected light is measured to obtain an infrared absorption spectrum (without ATR correction). If a part of the surface of the expanded beads to be measured is provided with a surface made of a polyethylene resin, the surface is brought into close contact with the prism. For example, in the case of cylindrical expanded beads produced by coextrusion, it is advisable to bring the outer peripheral surface of the cylinder, excluding the end faces, into close contact with the prism. <Measurement conditions> Prism: Zinc selenide Incident angle of infrared light: 45° Accumulation count: 512 times Resolution: 4cm -1 Detector: TGS (Triglycine sulfate) Measurement wavenumber range: 600~4000cm -1 Reflection count: 1 Incidentally, an example of a commercially available measuring device is FT / IR-4600 type A (ATR PRO450-S type) manufactured by JASCO Corp. Furthermore, the measurement may be macro measurement or micro measurement.
[0061] The infrared absorption spectrum of the cross section of the expanded bead 20 by the ATR method is measured by the following method. First, the expanded bead 20 is cut into approximately two equal parts passing through its center so that the volumes are approximately equal. Next, the infrared absorption spectrum of the cross section of the expanded bead 20 can be measured by the same method as that for measuring the infrared absorption spectrum of the surface of the expanded bead 20 described above, except that one of the cut surfaces is pressed against a prism.
[0062] When the infrared absorption spectrum of the expanded beads 20 is measured by the ATR method as described above, the following spectrum is detected. That is, wave number 2800~3200cm -1In the infrared absorption spectrum in, two absorbance peaks are detected on the surface of the expanded bead 20, and four absorbance peaks are detected on the cross section of the expanded bead 20. The fact that the above-mentioned number of absorbance peaks are exhibited on each of the surface and cross section of the expanded bead 20 means that the expanded bead 20 has an expanded bead body 21 made of a polypropylene-based resin composition and a surface 22 made of a polyethylene-based resin composition. Therefore, for the foamed particles of unknown composition, the infrared absorption spectrum of the surface and cross section was measured by the ATR method, and the wave number was 2800 to 3200 cm -1 It is advisable to check the number of absorbance peaks at 100 nm. This makes it possible to check whether the expanded beads used in the measurement have a foamed core layer made of a polypropylene-based resin as a base resin and a surface of the foamed core layer made of a polyethylene-based resin composition. In order to remove the influence of dust, dirt, organic matter, etc. attached to the surface of the expanded beads, the expanded beads may be washed before carrying out the ATR method described above.
[0063] The above wavenumbers 2800-3200 cm -1 More specifically, the following points are referred to with respect to the peaks exhibited by the expanded particles in the infrared absorption spectrum in Table 1. Note that, details of peaks 1 to 6 relating to the polyethylene resin and the polypropylene resin are shown in Table 1. That is, in the above measurement, the surface of the expanded beads 20 has a viscosity of 2920 cm -1 The peak appearing near 2850 cm (hereinafter referred to as Peak 1) -1 Peak 1 is a methylene group (-CH 2 Peak 2 is a peak derived from the antisymmetric stretching vibration of the methylene group (-CH 2 -) is a peak due to the symmetric stretching vibration. In the above measurement, the cross section of the expanded beads 20 had a thickness of 2950 cm -1The peak that appears near 2920 cm (hereinafter referred to as peak 3) -1 The peak that appears near 2870 cm (hereinafter referred to as peak 4) -1 The peak that appears near 2840 cm (hereinafter also referred to as peak 5) -1 Peak 3 is a peak that appears near the methyl group (-CH 3 Peak 4 is due to the asymmetric stretching vibration of the methylene group (-CH 2 Peak 5 is a peak derived from the antisymmetric stretching vibration of the methyl group (-CH 3 Peak 6 is a peak derived from the symmetric stretching vibration of the methylene group (-CH 2 -) is a peak due to the symmetric stretching vibration.
[0064] Therefore, four peaks (peaks 3 to 6) specific to polypropylene-based resins are observed in the cross section of the expanded beads 20, confirming that the expanded bead body 21 is composed of polypropylene-based resin as the base resin. Furthermore, two peaks (peaks 1 and 2) specific to polyethylene-based resins are observed in the surface of the expanded beads 20, confirming that the surface 22 is composed of a polyethylene-based resin composition containing polyethylene-based resin. In particular, -1 A peak (Peak 2) appearing nearby is a peak specific to polyethylene resins, and the appearance of Peak 2 confirms that surface 22 contains polyethylene resin.
[0065] As another method for confirming whether the surface of the expanded beads is composed of a polyethylene resin composition, the following method can be mentioned. Specifically, the infrared absorption spectrum of the surface of the expanded beads is measured by the ATR method described above. Then, at a wave number of 2950 cm -1 Absorbance A at 2950 Wave number for 2920 cm -1 Absorbance A at 2920Ratio of (A 2920 / A 2950 If the absorbance ratio is 2.0 or more, it can be determined that the foamed beads have a surface made of a polyethylene resin composition. -1 The appearance of the peak around this range is due to the methyl group (-CH 3 ) is due to the asymmetric stretching vibration of -1 The appearance of a peak around this range is common to polypropylene-based resins and polyethylene-based resins, and when a sample is mainly composed of a polypropylene-based resin as a base resin, the absorbance ratio is less than 2.0, whereas when a sample is mainly composed of a polyethylene-based resin, the absorbance ratio exceeds 2.0. This utilizes the general resin property. The upper limit of the absorbance ratio is approximately 10. In measuring the absorbance ratio, infrared absorption spectra are obtained for the surfaces of at least three expanded beads, and the arithmetic mean value of the obtained absorbance ratios is adopted.
[0066] The expanded beads 20 described above have excellent flame retardancy (FMVSS) and can exhibit excellent moldability in a mold even under low molding pressure conditions. Even if the bulk density of the expanded beads 20 is sufficiently low, the expanded beads 20 exhibit good fusion properties with each other during molding in a mold. Therefore, it is possible to produce a thick expanded bead molding or a rice-like expanded bead molding well.
[0067] [Method of manufacturing polypropylene resin foam particles] Next, the production method of the present invention will be described. The production method of the present invention is a preferred embodiment of the production method of the expanded polypropylene resin beads of the present invention. However, the production method of the expanded polypropylene resin beads of the present invention is not limited to the production method of the present invention.
[0068] As shown in FIG. 1, the production method of the present invention is a method in which multilayer particles (resin particles 10) are first granulated and then expanded to obtain expanded particles 20. Specifically, the manufacturing method of the present invention includes a coating process in which a polypropylene-based resin is used as a base resin and a core layer 11 containing a NOR-type hindered amine is coated with a polyethylene-based resin composition, and an expansion process in which resin particles 10 having a core layer 11 obtained by the coating process and a surface 12 composed of the polyethylene-based resin composition are expanded. The resin particles 10 granulated in the coating step have a NOR hindered amine content of 0.03% by weight or more and 0.5% by weight or less in the resin particles 10. The polyethylene resin composition is also prepared so that the NOR hindered amine content is less than the NOR hindered amine content in the resin particles 10 (including 0). The surface 12 becomes a surface 22 provided on the surface of the expanded bead 20 by expanding the resin bead 10 .
[0069] The expanded beads 20 of the present invention can be easily produced by the above-mentioned covering step and foaming step, and by adjusting the blending ratio of the NOR type hindered amine in the polyethylene resin composition constituting the core layer 11 and the surface layer 12 within an appropriate range. The production method of the present invention will be described in detail below.
[0070] (Coating process) As a method for coating the core layer 11 with the polyethylene resin composition in the coating step in the production method of the present invention, for example, the co-extrusion method or the mixing method described below can be mentioned.
[0071] Co-extrusion method: The co-extrusion method is as follows. First, a polypropylene resin composition for forming the core layer 11 is supplied to an extruder for forming the core layer. Then, the base resin and the like are melted in the extruder, and the melt is kneaded to obtain a melt-kneaded material for forming the core layer. On the other hand, a polyethylene resin composition for forming the surface 12 is supplied to an extruder for forming the surface, and the base resin and the like are melted in the extruder, and the melt is kneaded to obtain a melt-kneaded material for forming the surface. Next, in a co-extrusion die provided downstream of the extruder for forming the core layer, the melt-kneaded material for forming the core layer and the melt-kneaded material for forming the surface are merged, and the melt-kneaded material for forming the surface is laminated and extruded around the periphery of the melt-kneaded material for forming the core layer in the die to form a strand with a multilayer structure. Next, the strand is cut to a desired size by a pelletizer or the like, to obtain a resin particle 10 with a multilayer structure. The strand is a laminate having a cross section perpendicular to the extrusion direction, such as a circular shape. The resin particles 10 thus obtained are, for example, cylindrical or other columnar, with the core layer 11 provided at the center, no surface 12 on both end faces, and the surface 12 formed on the outer peripheral surface other than both end faces. In this manner, the core layer 11 may be exposed in part of the resin particles 10. The method of laminating the surface 12 on the surface of the core layer 11 by the co-extrusion method is preferred in that it is easy to adjust the weight ratio of the surface 12 in the resin particles 10, and that the surface 12 having a relatively uniform thickness can be formed on the resin particles 10 with good productivity. In the above co-extrusion method, when obtaining resin particles 10 having a multilayer structure, it is advisable to adjust the type of base resin of the surface 12, the weight ratio of the surface 12 in the resin particles 10, extrusion conditions, cutting conditions, etc. Then, for example, by adopting a method of cutting the strands in a state in which the strands are sufficiently softened, it is possible to obtain resin particles 10 in which the substantially entire surface of the core layer 11 is covered with the surface 12. Also, by subjecting the cylindrical resin particles 10 to a spheronization treatment, such as by heating the resin particles 10 in a dispersion medium at a temperature equal to or higher than the melting point of the base resin constituting the core layer 11 for a predetermined time, it is possible to obtain substantially spherical resin particles 10. When the above-mentioned co-extrusion method is employed in the coating step, the surface 12 is likely to be formed as a layer having a relatively uniform thickness. Therefore, this embodiment is suitable as a manufacturing method for forming the resin particles 10 having the coating layer 12S as the surface 12 and using the resin particles 10 to manufacture the expanded beads 20 having the coating layer 22S.
[0072] Mixing method: An example of a method for granulating the resin particles 10 as a mixing method is as follows. First, a polypropylene resin composition for forming the core layer 11 is supplied to an extruder for forming the core layer, and the base resin and the like are melted in the extruder while the molten material is kneaded to obtain a melt-kneaded material for forming the core layer. The melt-kneaded material for forming the core layer is extruded from the extruder to form a strand. Next, the strand is cut to a desired size by a pelletizer or the like to granulate the particulate core layer 11. Next, the particulate core layer 11 is put into a mixing device or the like having a mixing function and a heating function, and heated to heat the surface layer portion of the core layer 11. Next, a polyethylene resin composition containing a base resin and the like for forming the surface 12 is put into the mixing device or the like, and the heated particulate core layer 11 and the polyethylene resin composition are mixed, and the core layer 11 is covered with the polyethylene resin composition to obtain a resin particle 10 having a surface 12. This mixing method is preferable in that it is easy to form the surface 12 on the entire outer periphery of the core layer 11.
[0073] In the co-extrusion method or mixing method described above, the polypropylene resin composition and the melt kneaded product for forming the core layer obtained by melting the polypropylene resin composition contain a polypropylene resin, which is the base resin of the expanded bead main body 21 described above, and a NOR type hindered amine, and may optionally contain other additives such as a cell regulator and carbon black. The resin melt for forming the core layer is adjusted so that the blending ratio of the NOR type hindered amine in the resin particles 10 is 0.03% by weight or more and 0.5% by weight or less. On the other hand, the polyethylene resin composition and the molten kneaded product for surface formation obtained by melting the polyethylene resin composition contain at least a polyethylene resin, and may contain a NOR hindered amine in a proportion less than the NOR hindered amine blend proportion in the resulting expanded beads 20 (including 0), and may further contain other additives such as carbon black, if desired.
[0074] Adjustment of the crystalline state of foam particles: In order to adjust the crystalline state of the expanded beads 20 obtained, when the resin particles 10 are dispersed in an aqueous medium or when the resin particles 10 are impregnated with a blowing agent, the temperature rise rate in the sealed container may be adjusted, or the sealed container may be held at a predetermined temperature for a predetermined time. For example, it is possible to adjust the temperature so that an endothermic peak (high-temperature peak) appears on the higher temperature side than the endothermic peak (intrinsic peak) of the main component of the base resin constituting the body of the expanded beads 20 in a DSC curve obtained by heat flux differential scanning calorimetry. Expanded beads 20 showing such a high-temperature peak are preferable from the viewpoint of a wider range of molding conditions under which a good expanded bead molded body can be obtained. The temperature adjustment for obtaining the above-mentioned high-temperature peak can be performed, for example, as follows. In the above-mentioned dispersion step and / or blowing agent impregnation step, a one-stage holding step is performed in which a temperature is held at a temperature of (melting point of polypropylene-based resin -20°C) or more and less than (end of melting temperature of polypropylene-based resin) for about 10 to 60 minutes. Then, the temperature is adjusted to a temperature between (melting point of polypropylene resin -15°C) and less than (end of melting temperature of polypropylene resin). If necessary, a two-stage holding step is performed in which the temperature is held for another 10 to 60 minutes. Then, the foaming step described below is performed to produce expanded beads having a high-temperature peak. The total heat of fusion of the resulting expanded beads 20 is preferably 50 J / g to 90 J / g, more preferably 60 J / g to 80 J / g. The endothermic heat of the high-temperature peak (high-temperature peak heat) of the resulting expanded beads 20 is preferably 5 J / g to 40 J / g, more preferably 8 J / g to 30 J / g, and even more preferably 10 J / g to 20 J / g. The total heat of fusion and the high-temperature peak heat of the expanded beads 20 are determined based on JIS K7122:1987 from a DSC curve obtained by using 1 to 3 mg of the expanded beads as a test piece and heating the test piece from 23°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min.
[0075] (Foaming process) The resin particles 10 obtained in the coating step are used to carry out the expansion step. The expansion step can be carried out by appropriately selecting a known expansion method in which resin particles are impregnated with a foaming agent and expanded. For example, in the foaming step, the resin particles 10 are first dispersed in an aqueous medium in a sealed container. At this time, the sealed container may further contain an inorganic dispersant and other additives. Then, while dispersing the resin particles 10 in the sealed container, or after the dispersion is completed, a physical foaming agent is added to the sealed container to impregnate the resin particles 10 and obtain expandable resin particles. The addition of the physical foaming agent to the sealed container may be performed before the resin particles 10 are foamed. For example, when carbon dioxide is used as the physical foaming agent, it may be added in the form of dry ice to the aqueous medium together with the resin particles 10, or may be pressure-injected into the sealed container in a gaseous state. The impregnation of the physical foaming agent into the resin particles 10 is preferably performed under heating and / or pressure. The expandable resin particles obtained as described above are expanded by releasing them together with an aqueous medium under a pressure lower than the internal pressure of the sealed container, thereby obtaining the expanded particles 20.
[0076] Aqueous medium: Water is usually used as the aqueous medium for dispersing the resin particles 10, but for example, alcohols, glycols, glycerin, etc. can also be used. From the viewpoint of improving the dispersibility of the resin particles 10 and the productivity of the expanded beads 20, the amount of the resin particles 10 added to the aqueous medium is preferably 10 parts by weight or more and 100 parts by weight or less, and more preferably 20 parts by weight or more and 80 parts by weight or less, relative to 100 parts by weight of the aqueous medium.
[0077] Inorganic dispersants: As the inorganic dispersant, for example, inorganic fine particles such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, mica, etc. can be used. These inorganic fine particles may be used alone or in combination of two or more. Among these, it is preferable to use kaolin because of its excellent blocking suppression effect.
[0078] During the manufacturing process (particularly during the foaming process), the polyethylene resin constituting the surface 12 of the resin particles 10 is more likely to soften than the polypropylene resin constituting the core layer 11. As a result, the problem of blocking, in which the expanded particles are bonded to each other during foaming, is likely to occur. Therefore, compared to the case of manufacturing expanded particles whose surfaces are made of polypropylene resin, for example, in the manufacturing method of the present invention, it is preferable to add an appropriate amount of inorganic dispersant additive. From this viewpoint, in the manufacturing method of the present invention, the amount of inorganic dispersant added in the aqueous medium is preferably 0.05 parts by weight or more and 3 parts by weight or less, more preferably 0.1 parts by weight or more and 2 parts by weight or less, even more preferably 0.3 parts by weight or more and 1 part by weight or less, and particularly preferably 0.5 parts by weight or more and 0.8 parts by weight or less, relative to 100 parts by weight of the resin particles 10 to be mixed in the aqueous medium. Conventionally, the fusion property between expanded beads containing NOR type hindered amines is easily reduced. Although the reason for this is not clear, one of the reasons is that when a large amount of NOR type hindered amines are present on the surface of the expanded beads, the inorganic dispersant is easily attracted in an aqueous medium, and therefore the fusion property is easily deteriorated. That is, the expanded beads of the present invention are adjusted so that the blending ratio of the NOR type hindered amine in the polyethylene resin composition constituting the surface is smaller than the blending ratio of the NOR type hindered amine in the expanded beads, and as a result, the attraction of the inorganic dispersant on the surface of the expanded beads is suppressed, and it is considered that the fusion property between the expanded beads can be suppressed. Therefore, according to the present invention, even if an appropriate amount of the inorganic dispersant additive is added in the manufacturing process, such as within the above range, the expanded beads exhibit good fusion property.
[0079] Other Additives: The aqueous medium may further contain one or more optional additives such as a dispersion aid and a surfactant in addition to the inorganic dispersant. Examples of the dispersion aid include aluminum sulfate. Examples of the surfactant include anionic surfactants such as sodium alkylbenzenesulfonate, sodium dodecylbenzenesulfonate, and sodium alkanesulfonate. The surfactant may be used alone or in combination of two or more.
[0080] Physical foaming agent: As the physical foaming agent, inorganic physical foaming agents and / or organic physical foaming agents can be used. Examples of inorganic physical foaming agents include carbon dioxide, air, nitrogen, helium, argon, water, etc. Examples of organic physical foaming agents include aliphatic hydrocarbons such as propane, butane, and hexane, alicyclic hydrocarbons such as cyclopentane and cyclohexane, and halogenated hydrocarbons such as methyl chloride, ethyl chloride, methylene chloride, 2,3,3,3-tetrafluoropropene, trans-1,3,3,3-tetrafluoropropene, and trans-1-chloro-3,3,3-trifluoropropene, etc.
[0081] These physical foaming agents may be used alone or in combination of two or more. Of these foaming agents, preferably, foaming agents mainly composed of inorganic physical foaming agents such as carbon dioxide, nitrogen, and air are used, and more preferably, carbon dioxide is used. In the present invention, "mainly composed of inorganic physical foaming agent" means that the physical foaming agent contains 50 mol% or more of inorganic physical foaming agent. It is preferable that the physical foaming agent contains 70 mol% or more of inorganic physical foaming agent, more preferably 90 mol% or more, and it is even more preferable that the physical foaming agent consists of only inorganic physical foaming agent.
[0082] The amount of the physical foaming agent added is appropriately selected depending on the type of polyolefin resin, the type of foaming agent, the targeted bulk density of the expanded particles, etc. For example, when carbon dioxide is used as the physical foaming agent, the amount of carbon dioxide added is preferably 0.1 to 30 parts by weight, more preferably 0.5 to 15 parts by weight, and even more preferably 1 to 10 parts by weight, per 10 or 100 parts by weight of the resin particles.
[0083] Bulk density adjustment: The bulk density of the expanded beads 20 can be adjusted, for example, by appropriately changing the expansion conditions, such as the temperature and pressure in the sealed container, when the content of the sealed container is released in the expansion process. Furthermore, when expanded beads 20 having a lower bulk density are desired, a step of expanding the expanded beads in multiple stages may be carried out, such as the two-stage expansion step described below. In the two-stage expansion step, the expanded beads 20 obtained as described above are first stored in a pressurizable sealed container, and a gas such as air is forced into the sealed container to perform a pressurization treatment and increase the internal pressure in the bubbles of the expanded beads 20. Thereafter, the expanded beads 20 are taken out of the sealed container, and heated with steam or hot air to expand the expanded beads 20, thereby carrying out the two-stage expansion. By carrying out such a two-stage expansion step, it is possible to obtain expanded beads 20 (two-stage expanded beads) having a lower bulk density. In addition, compared with obtaining expanded beads 20 having a low bulk density by a single expansion step, obtaining expanded beads 20 having a low bulk density by performing a two-stage expansion step makes it easier to increase the cell diameter of the finally obtained expanded beads 20. The expanded bead molding produced using the expanded beads 20 obtained by performing the two-stage expansion step can more effectively suppress the occurrence of uneven color tone.
[0084] [Different manufacturing methods for foamed beads] The expanded beads 20 may be produced by a production method (hereinafter also referred to as a second production method) different from the production method of the present invention described above. The second manufacturing method, not shown, is a method in which first, the resin bead body that becomes the expanded bead body 21 is granulated, and then expanded to obtain the expanded bead body 21. The expanded bead body 21 is then coated with a polyethylene-based resin composition to obtain the expanded bead 20 having a surface 22.
[0085] In other words, the second manufacturing method includes an expansion step in which a polypropylene-based resin is used as a base resin and a resin bead body containing a NOR-type hindered amine is expanded to obtain an expanded bead body 21, and a coating step in which the expanded bead body 21 obtained by the expansion step is coated with a polyethylene-based resin composition. In the second production method as well, the blending ratio of the NOR type hindered amine in the obtained expanded beads 20 is adjusted to be 0.03% by weight or more and 0.5% by weight or less, and the blending ratio of the NOR type hindered amine in the polyethylene resin composition constituting the surface 22 is adjusted to be less than the blending ratio of the NOR type hindered amine in the expanded beads 20. The blending ratio of the NOR type hindered amine in the polyethylene resin composition constituting the surface 22 may be 0% by weight.
[0086] In the expansion step of the second production method, for example, a molten material similar to the molten mixture for forming the core layer in the production method of the present invention described above is extruded from an extruder to prepare strands, which are then cut to a desired size to granulate the resin bead bodies. The resin bead bodies are then expanded by a known expansion method to obtain the expanded bead bodies 21. The coating step in the second manufacturing method is carried out using the expanded bead body 21 obtained as described above. For this coating step, the mixing method in the manufacturing method of the present invention is referred to as appropriate. As an example, the expanded bead body 21 is charged into a mixer having a mixing function and a heating function, and heated, and then a powdered polyethylene resin composition for forming the surface 22 is charged. The expanded bead body 21 and the polyethylene resin composition are then mixed, and the surface of the expanded bead body 21 is coated with the polyethylene resin composition, thereby obtaining an expanded bead 20 having a surface 22.
[0087] [Foamed bead molding] An expanded bead molding can be obtained by in-mold molding using the expanded beads 20 of the present invention. Specifically, the expanded bead molding is produced as follows. First, the expanded beads are filled into a mold having a cavity corresponding to the shape of the desired expanded bead molding, and the expanded beads 20 filled in the mold are heated by a heating medium such as steam. The expanded beads 20 in the cavity are further expanded by heating and are fused to each other. As a result, the expanded beads 20 are integrated with each other, and an expanded bead molding corresponding to the shape of the cavity is obtained. The expanded bead molding produced using the expanded beads 20 enjoys the effects of the present invention, exhibits good flame retardancy, and is also excellent in fusion bonding properties, and can therefore be suitably used in various applications requiring flame retardancy, such as packaging materials, automobile parts, building materials, and electrical and electronic products.
[0088] Flame Retardant: The flame retardancy of expanded bead moldings can be evaluated based on the position at which burning ends, the duration of burning, and the burning distance when a flammability test is conducted according to FMVSS (Federal Motor Vehicle Safety Standard) No. 302. The flammability test method according to FMVSS No. 302 is specifically as follows:
[0089] First, the expanded beads 20 are molded in a mold, and then a plate-shaped test specimen is cut out from the resulting expanded bead molding. Next, the test specimen is left for 24 hours in an environment with a temperature of 23°C and a relative humidity of 50% to condition the test specimen. After the condition is conditioned, a start line is drawn on the test specimen at a position 38 mm away from the base end in the length direction, and an end line is drawn at a position 292 mm away from the base end. Next, the test specimen is attached to the U-shaped frame of a chamber dedicated to FMVSS No. 302. Next, the burner is ignited, and the amount of gas and air is adjusted so that the flame height is 38 mm. In this state, the burner is moved so that the center of the tip of the burner is at the center of the width direction at the base end of the test specimen, and the burner flame is kept in contact with the test specimen for 15 seconds. After that, the burner flame is removed from the test specimen, and the duration of combustion is measured from when the test specimen's combustion position reaches the start line until the combustion ends.
[0090] In this specification, the degree of flame retardancy of the expanded bead molding is classified into one of three stages: self-extinguishing, retarded, and flammable. Specifically, if the combustion of the test specimen ends before reaching the initiation line, or if the combustion end position of the test specimen is within 50 mm from the initiation line and the combustion duration is within 60 seconds, the expanded bead molding is judged to have self-extinguishing properties. If the expanded bead molding does not fall under the above-mentioned self-extinguishing properties and the burning speed obtained by dividing the burning distance from the initiation line by the burning duration is less than 80 mm / min, the expanded bead molding is judged to have retarded flame. If the expanded bead molding does not fall under the above-mentioned self-extinguishing properties and the burning speed is 80 mm / min or more, the expanded bead molding is judged to have flammability.
[0091] The expanded bead molding preferably has flame retardancy, and more preferably has self-extinguishing properties, when subjected to a flammability test specified in FMVSS No. 302. The expanded bead molding exhibiting flame retardancy or self-extinguishing properties can be suitably used in applications requiring high flame retardancy. In particular, the expanded bead molding exhibiting self-extinguishing properties is suitable for applications such as automobile components and building materials.
[0092] Molded body density: The density of the expanded bead molding obtained by using the expanded beads 20 is not particularly limited. From the viewpoint of excellent balance between light weight and mechanical properties such as rigidity, the density is preferably 10 kg / m 3 More than 500kg / m 3 It is preferable that the thickness is less than 15 kg / m 3 More than 100kg / m 3 The molding density of the expanded bead molding is calculated by dividing the weight of the expanded bead molding by the volume calculated based on the external dimensions. When it is difficult to calculate the volume from the external dimensions, the volume of the expanded bead molding can be determined by a submersion method.
[0093] The expanded beads 20 have excellent fusion properties as described above. In particular, even when an expanded bead molding having a thicker portion or a rice-shaped expanded bead molding is molded in a mold, the expanded bead molding has excellent fusion properties. Therefore, for example, a polypropylene resin expanded bead molding can be provided that is formed by molding the expanded beads 20 in a mold, the expanded bead molding has a portion with a thickness of 80 mm or more, has a fusion rate of 80% or more, and exhibits a flame retardant property or self-extinguishing property with a burning rate of less than 80 mm / min according to FMVSS No. 302. The expanded bead molding can have a portion with a thickness of 90 mm or more, and can further have a portion with a thickness of 100 mm or more. In addition, the expanded bead molding can be cut into a sphere with a diameter of 80 mm. The fusion rate of the expanded bead molding can be determined as the ratio of the number of expanded beads that have been broken out of the number of expanded beads exposed on the fracture surface when the expanded bead molding is broken. EXAMPLES
[0094] The present invention will be described in detail below with reference to examples. In these examples, the manufacturing method of the present invention is carried out to manufacture expanded beads. In particular, a co-extrusion method is selected as the coating step, and the surface of both the resin particles and the surface of the expanded beads are described as an example. However, the present invention is not limited thereto. For each of the Examples and Comparative Examples carried out as described below, the bulk density, total heat of fusion, high-temperature peak heat, average cell diameter, and absorbance by the ATR method of the expanded beads were measured, and the polypropylene resin expanded bead moldings produced using the expanded beads were evaluated. The measurement results and evaluation results are shown in Tables 3 and 4. The method for measuring the bulk density and the method for evaluation will be described later. In the tables, carbon black is written as CB. The expanded beads used for measuring the physical properties of the expanded beads were left to stand for 24 hours or more in an environment of 23°C temperature, 50% relative humidity, and 1 atm to condition them. In addition, the blending proportion of the NOR hindered amine in the expanded beads and the coating layer of the expanded beads, the blending proportion of the NOR hindered amine in the expanded beads, and the ratio of the blending proportion of the NOR hindered amine in the coating layer to the blending proportion of the NOR hindered amine in the expanded beads were calculated from the blending proportions of the materials used in producing the resin beads.
[0095] <Example 1> (Preparation of resin particles) A manufacturing device was prepared, which was equipped with an extruder for forming a core layer with an inner diameter of 50 mm, a die for forming a multilayer strand attached to the downstream side of the extruder for forming a core layer, and an extruder for forming a coating layer with an inner diameter of 30 mm. Note that the downstream side of the extruder for forming a coating layer was connected to the die for forming a multilayer strand, and the manufacturing device was configured to be capable of laminating the molten mixture for forming each layer in the die and to be capable of co-extrusion. The core layer molding material (polypropylene-based resin composition) constituting the core layer was made of the polypropylene-based resin (PP1) shown in Table 2, and in addition, 0.1 wt% zinc borate was used as a bubble regulator in 100 wt% of the core layer molding material, and carbon black (furnace black) and NOR-type hindered amine (manufactured by BASF, product name NOR116 (molecular weight 2261)) were used in the blending ratios shown in Table 3. These were supplied to an extruder for forming the core layer and melt-kneaded. As the coating layer forming material (polyethylene resin composition) constituting the coating layer, in addition to the polyethylene resin (PE1) shown in Table 2, carbon black (furnace black) was used in the blending ratio shown in Table 3, and these were fed into a coating layer forming extruder and melt-kneaded. The molten mixtures for forming each layer obtained by melt kneading as described above were introduced into a die for forming a multilayer strand and merged inside the die, and a multilayer strand having a two-layer structure (coating layer / core layer structure) was extruded from the holes in the die attached to the downstream side of the die. The extruded strand was cooled with water and cut with a pelletizer to obtain resin particles with an average weight of 1.0 mg per piece.
[0096] (Preparation of Expanded Beads) 1 kg of the obtained resin particles was supplied together with 3 L of water as an aqueous medium into a sealed container having a capacity of 5 L. Furthermore, 0.6 parts by weight of kaolin as an inorganic dispersant, 0.008 parts by weight (as an active ingredient) of a surfactant (product name: NEOGEN, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., sodium dodecylbenzenesulfonate), and 0.02 parts by weight of aluminum sulfate were each added to the sealed container relative to 100 parts by weight of the resin particles. Next, carbon dioxide was injected as a blowing agent into the sealed container, and the pressure was increased to 3.1 MPa (G) in gauge pressure. The pressures marked with (G) are gauge pressures, that is, pressure values based on atmospheric pressure. After that, the sealed container was heated to the foaming temperature (137.5°C) at a temperature increase rate of 2°C / min while stirring, and the temperature was maintained for 15 minutes. This was adjusted so that a high-temperature peak would appear on the endothermic curve of the resulting expanded beads measured by DSC. The contents of the sealed container (resin particles and water) are then released under atmospheric pressure to a bulk density of 60 kg / m 3 The same process as described above was repeated several times to obtain a sufficient amount of expanded beads for the evaluation described below.
[0097] The first-stage expanded particles obtained as described above were left to stand for 24 hours in an environment of 23°C temperature, 50% relative humidity, and 1 atm for curing. The cured first-stage expanded particles were then filled into a pressurizable airtight container, and the pressure in the airtight container was increased from normal pressure to pressurize the expanded particles. The pressurized state of the expanded particles was maintained for a predetermined time, allowing air to be impregnated into the bubbles of the expanded particles. The first-stage expanded particles were then removed from the airtight container, and first-stage expanded particles with an internal bubble pressure of 0.5 MPa (G) were obtained. The first-stage expanded particles were then fed into a second-stage expansion device. Steam was fed into the device to expand the first-stage expanded particles, resulting in a bulk density of 27 kg / m 3 The expanded beads obtained by the two-stage expansion were used for the following measurements and for producing expanded bead moldings.
[0098] (bulk density of expanded particles) The expanded particles to be measured were left to cure for 24 hours or more in an environment of 23°C temperature, 50% relative humidity, and 1 atm. The cured expanded particles (weight W; 30 g) were filled into a measuring cylinder, and the bottom of the measuring cylinder was lightly tapped on the floor several times to stabilize the filling height of the expanded particles in the measuring cylinder. The bulk volume V (L) of the expanded particles indicated by the graduations on the measuring cylinder was read. The weight W of the expanded particles was then divided by the bulk volume V (W / V). The value obtained in this way was expressed in kg / m 3 The bulk density of the foamed particles (kg / m 3 ) was calculated.
[0099] (Total heat of fusion and high-temperature peak heat of expanded particles) The test specimen was approximately 1 mg of foamed particles. The test specimen was heated and melted according to the method for measuring the heat of transition of plastics described in JIS K7122:1987, and a DSC curve was obtained. The measurement temperature range was from 23°C to a temperature 30°C higher than the end of the melting peak of the test specimen, and the heating rate was 10°C / min. The DSC curve thus obtained is shown in Figure 3. A straight line was drawn on the DSC curve connecting point I, which corresponds to 80°C on the DSC curve, and point II, which corresponds to the melting end temperature of the expanded beads. The melting end temperature is the high-temperature end point of high-temperature peak b, and is the intersection point of high-temperature peak b and the baseline on the higher temperature side of high-temperature peak b on the DSC curve. As shown in Figure 3, a straight line was drawn connecting points I and II, and then the intersection point of the line passing through the maximum point III between the intrinsic peak a and the high-temperature peak b and parallel to the vertical axis of the graph with the line connecting points I and II was designated as IV. The areas of the straight line connecting points I and IV, the straight line connecting points III and IV, and the DSC curve connecting points I and III were defined as the area of intrinsic peak a. The area of the portion (shaded portion) surrounded by the straight line connecting points IV and II, the straight line connecting points III and IV, and the DSC curve connecting points III and II was defined as the area of high-temperature peak b. The sum of the areas of intrinsic peak a and high-temperature peak b determined as above was defined as the value of the total heat of fusion of the expanded beads, and the area of high-temperature peak b was defined as the value of the high-temperature peak heat of the expanded beads.
[0100] (Average bubble diameter of expanded particles) A photograph of the cross section of an expanded bead divided into two was taken. A straight line was drawn on the photograph so as to roughly halve the area of the expanded bead cross section, and the length L of the line segment from one edge of the expanded bead to the opposite edge was divided by the number N of all the bubbles in contact with the line segment (L / N) to determine the average bubble diameter of one expanded bead. This operation was performed for 10 or more expanded beads, and the arithmetic average value was determined to be the average bubble diameter of the expanded beads.
[0101] (ATR analysis of foam particles) Measurement was performed by macro ATR. The foamed particles obtained above were analyzed using a commercially available ATR analyzer (manufactured by JASCO Corporation; FT / IR-4600 type A (ATR PRO450-S type)). The analysis conditions were as follows. <Measurement conditions> Prism: Zinc selenide Incident angle of infrared light: 45° Accumulation count: 512 times Resolution: 4cm -1 Detector: TGS (Triglycine sulfate) Measurement wavenumber range: 600~4000cm -1 Reflection count: 1
[0102] The surface of the expanded beads was analyzed by bringing the outer peripheral surface of the expanded beads, excluding both end faces, into contact with a prism, while the cross section of the expanded beads was analyzed by bringing the cut surface into contact with a prism using a sample cut at approximately half the positions of both end faces of the expanded beads in a direction perpendicular to the axial direction of the column. In the ATR analysis, the wavenumbers of the foamed particle surface and cross section were 2800 to 3200 cm -1 The number of absorbance peaks and the absorbance of the peaks at wavenumber 2950 cm were also measured. -1 Absorbance A at 2950 Wave number for 2920 cm -1 Absorbance A at 2920 Ratio of (A 2920 / A 2950 ) was obtained. In all of the Examples and Comparative Examples 2 and 3, two peaks were detected on the expanded bead surface (peaks 1 and 2 shown in Table 1), and four peaks were detected on the expanded bead cross section (peaks 3 to 6 shown in Table 1). That is, it was confirmed that in all of the expanded beads, polypropylene-based resin was present in the cross section, and polyethylene-based resin was present on the surface. In Comparative Example 1, four peaks were detected on both the expanded bead surface and the expanded bead cross section (peaks 3 to 6 shown in Table 1). That is, it was confirmed that polypropylene-based resin was present in both the cross section and the surface of the expanded bead of Comparative Example 1, which is a single layer. In addition, in all of the Examples and Comparative Examples 2 and 3, the ratio of absorbance on the surface of the expanded beads (A 2920 / A 2950 ) was 2.0 or more. That is, it was confirmed that the polyethylene resin was present on the surface of each of the expanded beads. In addition, in Comparative Example 1, the ratio of absorbance (A 2920 / A 2950 ) was less than 2.0. That is, it was confirmed that the polypropylene-based resin was present both on the cross section and on the surface of the expanded beads of Comparative Example 1, which was a single layer. In measuring the absorbance ratio, infrared absorption spectra were obtained for the surfaces of three expanded beads, and the arithmetic average value of the obtained absorbance ratios was used.
[0103] (Production of foamed bead moldings) The obtained expanded beads were filled into a pressurizable sealed container, and the pressure in the sealed container was increased from normal pressure to pressurize the expanded beads. The expanded beads were kept in a pressurized state for a predetermined time to impregnate the bubbles of the expanded beads with air. Thereafter, the expanded beads were taken out of the sealed container to obtain expanded beads with an internal pressure of 0.1 MPa (G) in the bubbles of the expanded beads. The obtained expanded beads were filled into a mold (die) having a flat molding cavity with a length of 350 mm, a width of 200 mm, and a thickness of 50 mm in the mold opening direction, and heated by the following heating method. The heating method was to supply steam to the die with the drain valves on both sides of the die open to perform preheating (exhaust process). Thereafter, steam was supplied from one side of the die to heat it, and further steam was supplied from the other side of the die to heat it. Subsequently, steam of 0.20 MPa (G) was supplied from both sides of the die to heat it. After the heating, the pressure was released and the expanded bead molding was cooled with water until the surface pressure due to the expanding force of the expanded bead molding became 0.04 MPa (G), and then the mold was opened and the expanded bead molding was taken out. The expanded bead molding obtained was cured in an oven at 80°C for 12 hours and then slowly cooled to room temperature to obtain a plate-shaped expanded polypropylene resin bead molding.
[0104] <Example 2> Resin particles were prepared in the same manner as in Example 1, except that a NOR-type hindered amine (manufactured by BASF, product name NOR116 (molecular weight 2261)) was added to the coating layer forming material in the blending ratio shown in Table 3. Using these resin particles, a foamed bead molding was obtained in the same manner as in Example 1.
[0105] <Example 3> Resin particles were prepared in the same manner as in Example 1, except that the amount of NOR-type hindered amine added to the core layer molding material was changed to the blending ratio shown in Table 3. Using these resin particles, a foamed bead molding was obtained in the same manner as in Example 1.
[0106] <Example 4> Resin particles were prepared in the same manner as in Example 1, except that the type of polyethylene resin added to the coating layer-forming material was changed to PE2 shown in Table 2. Using these resin particles, a foamed bead molding was obtained in the same manner as in Example 1.
[0107] <Example 5> Resin particles were prepared by the same operation as in Example 1. Using these resin particles, expanded beads were produced in the same manner as in Example 1, except that the expansion temperature and the blowing agent impregnation pressure were changed to the values shown in Table 3, and that the two-stage expansion was not performed, to obtain expanded beads having a higher bulk density than in Example 1. Using these expanded beads, molding was performed in a mold at the molding pressure shown in Table 3 to obtain a rice-rice-shaped expanded bead molding.
[0108] <Example 6> Resin particles were prepared by the same operation as in Example 1. Using these resin particles, an expanded bead molding was obtained by the same method as in Example 1, except that the molding die was changed to a molding die (metal mold) having a flat molding cavity of 350 mm length × 200 mm width × 100 mm thickness in the mold opening direction, and the molding pressure was changed to the value shown in Table 3. In Example 6, a thick expanded bead molding was obtained.
[0109] <Example 7> Except for not blending carbon black in either the core layer forming material or the coating layer forming material, resin particles were prepared in the same manner as in Example 1. Using these resin particles, a foamed bead molding was obtained in the same manner as in Example 1.
[0110] <Example 8> Resin particles were prepared in the same manner as in Example 1, except that the amount of NOR-type hindered amine added to the core layer molding material was changed to the blending ratio shown in Table 3. Using these resin particles, an expanded bead molding was obtained in the same manner as in Example 1. In Comparative Example 8, slight unevenness in color tone occurred compared to Example 1.
[0111] <Example 9> Resin particles were prepared in the same manner as in Example 1, except that the type of NOR-type hindered amine added to the core layer-forming material was changed to the type shown in Table 3 (product name FP-T80 (molecular weight 681, manufactured by ADEKA Corporation)). Using these resin particles, a foamed bead molding was obtained in the same manner as in Example 1.
[0112] <Comparative Example 1> Except for not providing a coating layer and using a core layer-forming material to form a single layer of particles, resin particles were prepared in the same manner as in Example 1. Using these resin particles, a foamed bead molding was obtained in the same manner as in Example 1. The obtained expanded beads did not have a coating layer, and the blending ratio of NOR type hindered amine on the surface was equal to the blending ratio of NOR type hindered amine in the entire expanded beads, so the fusion properties of the expanded bead moldings produced using them were poor.
[0113] <Comparative Example 2> Resin particles were prepared in the same manner as in Example 5, except that the type of polyethylene resin added to the coating layer-forming material was changed to PE2 shown in Table 2 and that a NOR-type hindered amine was added to the coating layer-forming material. Using these resin particles, a rice-shaped expanded bead molding was obtained in the same manner as in Example 5. In Comparative Example 2, the blending ratio of NOR type hindered amine in the coating layer forming material was higher than the blending ratio of NOR type hindered amine in the core layer forming material, the fusion properties of the expanded bead molding were insufficient, and the tensile strength was lower than that of Example 5.
[0114] <Comparative Example 3> Except for adding a NOR type hindered amine to the coating layer forming material, resin particles were prepared in the same manner as in Example 6. Using these resin particles, a thick foamed molded article was obtained in the same manner as in Example 6. In Comparative Example 3, the blending ratio of the NOR type hindered amine in the coating layer forming material was higher than the blending ratio of the NOR type hindered amine in the core layer forming material, and the fusion property of the expanded bead molding was poor.
[0115] <Evaluation of Molded Products> The molded products of each of the Examples and Comparative Examples were evaluated as follows. The molding pressure (MPa(G)) during molding in the mold is also shown in Tables 3 and 4.
[0116] Density of foamed bead compacts: The weight of the expanded bead molding is divided by the volume calculated based on the dimensions to give the molding density (kg / m 3 ) was decided.
[0117] Weldability: The fusion property of the expanded bead molding was determined based on the ratio of the number of foamed beads that were broken among the foamed beads exposed on the fracture surface when the expanded bead molding was broken. Specifically, first, a test piece (150 mm long x 75 mm wide x 25 mm thick) was cut out from the vicinity of the center in the thickness direction of the expanded bead molding, and a cutter knife was used to make a cut of about 2 mm across the entire width in the thickness direction of each test piece. Next, using the test piece, a three-point bending test was performed in accordance with JIS K7221-2 (2006) under conditions of a support distance of 70 mm and a pressure wedge speed of 200 mm / min, and the test piece was pressed until it broke. Next, the number (n) of foamed beads present on the fracture surface of the expanded bead molding and the number (b) of foamed beads that were broken were measured, and the ratio (b / n) of (b) and (n) was expressed as a percentage to obtain the fusion rate (%), and was evaluated as follows. ○: Fusion rate is 80% or more. △: Fusion rate is less than 80% and more than 40%. ×: Fusion rate is less than 40%.
[0118] Tensile strength: The tensile strength (kPa) of the expanded bead molding was measured in accordance with JIS K6767:1999. A vertical slicer was used to cut out a 120 mm x 25 mm x 10 mm piece from the expanded bead molding so that all surfaces were cut out, and a jigsaw was used to prepare a dumbbell-shaped No. 1 test piece from the cut out piece, which was then subjected to a tensile test at a tensile speed of 500 mm / min to determine the tensile strength. The maximum tensile stress during tension was taken as the tensile strength.
[0119] Flammability: The flame retardancy of the expanded bead molding was evaluated by a method conforming to the flammability test method specified in FMVSS No. 302. Specifically, the expanded bead molding was first cut to produce a test specimen having a plate shape of 150 mm in length, 102 mm in width, and 12.7 mm in thickness, with one side surrounded by a side of 150 mm in length and a side of 102 mm in width being a skin surface. A start line was drawn 38 mm away from the base end in the length direction of this test specimen, and an end line was drawn 292 mm away from the base end. Using this test specimen, a flammability test was performed by the same method as FMVSS No. 302, with the skin surface in contact with the flame of a burner. The test specimen was then evaluated as follows. ◎: Showed self-extinguishing properties. Good: The burning rate was less than 80 mm / min. ×: The burning rate was 80 mm / min or more.
[0120] Color Tone Unevenness (Appearance): Thirty measurement positions were randomly set on the plate surface of the foamed bead molding. The color tones at these measurement positions were measured using a spectrophotometer ("CM-5" manufactured by Konica Minolta Japan, Inc.) to obtain color coordinates in the CIE 1976 L*a*b* color space. The color tones were obtained by reflection measurement, the measurement diameter was φ8 mm, and the measurement method was the SCE method. The difference between the maximum and minimum L* values in the color coordinates obtained at the 30 measurement positions described above was evaluated according to the following criteria. The L* value is an index of brightness, and the larger the value, the brighter the image. The smaller the difference between the maximum and minimum L* values, the smaller the difference in brightness and the smaller the color unevenness. In addition, the foamed bead moldings in each of the comparative examples were poor in either fusion property or surface property, so that they were not evaluated for uneven color tone. ◎: The difference between the maximum and minimum L* values is less than 5 〇: The difference between the maximum and minimum L* values is 5 or more
[0121] [Table 1]
[0122] [Table 2]
[0123] [Table 3]
[0124] [Table 4]
[0125] The above embodiment encompasses the following technical ideas. (1) A polypropylene-based resin foam particle containing a NOR type hindered amine, The polypropylene-based resin foamed particles have a surface composed of a polyethylene-based resin composition containing a polyethylene-based resin, The blending ratio of NOR type hindered amine in the polypropylene resin foam particles is 0.03% by weight or more and 0.5% by weight or less, The expanded polypropylene resin particles are characterized in that the blending ratio of the NOR type hindered amine in the polyethylene resin composition is smaller (including 0) than the blending ratio of the NOR type hindered amine in the expanded polypropylene resin particles. (2) before The expanded polypropylene resin particles according to the above (1), wherein the content of the NOR type hindered amine in the polyethylene resin composition is 0.2% by weight or less (including 0). (3) The expanded polypropylene resin particles according to (1) or (2) above, wherein the ratio of the NOR type hindered amine in the expanded polypropylene resin particles to the NOR type hindered amine in the polyethylene resin composition is 0.5 or less. (4) The above PolyThe expanded polypropylene resin particles according to any one of (1) to (3) above, wherein the expanded polypropylene resin particles have an average cell diameter of 50 μm or more and 220 μm or less. (5) The above Poly The bulk density of the propylene resin foam particles is 10 kg / m 3 More than 500kg / m 3 The polypropylene resin expanded particles according to the above (1) or (4), which are as follows: (6) The expanded polypropylene resin particles according to any one of (1) to (5) above, wherein the polyethylene resin composition contains a linear low-density polyethylene polymerized using a metallocene polymerization catalyst. (7) a coating step of coating a polyethylene resin composition on a core layer containing a polypropylene resin as a base resin and a NOR type hindered amine; and a foaming step of foaming polypropylene-based resin particles having the core layer obtained in the coating step and a surface composed of the polyethylene-based resin composition to obtain foamed polypropylene-based resin particles, The method for producing expanded polypropylene-based resin particles is characterized in that the blending ratio of NOR type hindered amine in the polypropylene-based resin particles is 0.03% by weight or more and 0.5% by weight or less, and the blending ratio of NOR type hindered amine in the polyethylene-based resin composition is less than the blending ratio of NOR type hindered amine in the polypropylene-based resin particles (however, 0 is included). (8) A polypropylene resin expanded bead molding obtained by molding the polypropylene resin expanded bead according to any one of (1) to (6) above in a mold. (9) The expanded polypropylene resin bead molding according to claim 8, which has a portion with a thickness of 80 mm or more, a fusion rate of 80% or more, and exhibits flame retardancy or self-extinguishing properties such that the burning rate obtained in accordance with FMVSS No. 302 is less than 80 mm / min. [Explanation of symbols]
[0126] 10. Resin particles 11...Core layer 12, 22... surface 12S, 22S...covering layer 20...Polypropylene resin foam particles 21... Foam particle body 30, 30A, 30B...Surface layer
Claims
1. A polypropylene-based resin foamed particle containing a NOR type hindered amine, The polypropylene-based resin foamed particles have a surface composed of a polyethylene-based resin composition containing a polyethylene-based resin, the blending ratio of NOR type hindered amine in the polypropylene-based resin foamed beads is 0.03% by weight or more and 0.5% by weight or less; The expanded polypropylene resin particles are characterized in that the blending ratio of the NOR type hindered amine in the polyethylene resin composition is smaller (including 0) than the blending ratio of the NOR type hindered amine in the expanded polypropylene resin particles.
2. Polypropylene-based resin foam particles as described in claim 1, wherein the blending ratio of NOR-type hindered amine in the polyethylene-based resin composition is 0.2 weight % or less (including 0).
3. 3. The expanded polypropylene resin beads according to claim 1, wherein the ratio of the NOR hindered amine in the polyethylene resin composition to the NOR hindered amine in the expanded polypropylene resin beads is 0.5 or less.
4. The expanded polypropylene resin particles according to claim 1 , wherein the expanded polypropylene resin particles have an average cell diameter of 50 μm or more and 220 μm or less.
5. The bulk density of the polypropylene resin foam particles is 10 kg / m 3 More than 100kg / m 3 The expanded polypropylene resin particles according to any one of claims 1 to 4, wherein:
6. The expanded polypropylene resin particles according to claim 1 , wherein the polyethylene resin composition contains a linear low-density polyethylene polymerized using a metallocene polymerization catalyst.
7. A coating step of coating a polyethylene resin composition on a core layer containing a polypropylene resin as a base resin and a NOR hindered amine; and a foaming step of foaming polypropylene-based resin particles having the core layer obtained in the coating step and a surface composed of the polyethylene-based resin composition to obtain foamed polypropylene-based resin particles, A method for producing expanded polypropylene-based resin beads, characterized in that, in the polypropylene-based resin particles, a blending ratio of a NOR-type hindered amine in the polypropylene-based resin particles is 0.03% by weight or more and 0.5% by weight or less, and a blending ratio of a NOR-type hindered amine in the polyethylene-based resin composition is less than a blending ratio of a NOR-type hindered amine in the polypropylene-based resin particles (however, the blending ratio may be 0).
8. 7. A polypropylene resin expanded bead molding obtained by molding the expanded polypropylene resin beads according to claim 1 in a mold.
9. The polypropylene resin foamed bead molding according to claim 8, which has a thickness of 80 mm or more, a fusion rate of 80% or more, and a flame retardant or self-extinguishing property such that the burning rate according to FMVSS No. 302 is less than 80 mm / min.
Citation Information
Patent Citations
Expanded resin bead
JP1998077359A
In-mold foam molding of polyolefin-based resin
JP2004263033A
Seal-material sheet for solar battery module and solar battery module arranged by use thereof
JP2019062132A